Clusters of potential autonomous vehicles users according to propensity to use individual versus shared vehicles - Pettigrew, Simone; Norman, Richard; Dana, Liyuwork (2019)
© 2019 As the widespread use of autonomous vehicles (AVs) becomes increasingly likely, an important consideration is the extent to which individuals prefer either private ownership or shared use modes. Both modes are currently evolving, each with distinct but overlapping challenges. Understanding the preferences of different population segments can provide insights into where to focus initial efforts to attract individuals into the market, especially in terms of promoting the uptake of shared AVs to optimise the potential positive outcomes of AVs (e.g., crash reduction) while reducing possible negative outcomes (e.g., increased congestion). The results from a sample of 1345 Australians aged 16+ years (97% of whom were drivers) were analysed using latent profile analysis. Five discrete classes were identified on the basis of their (i) self-reported knowledge of AVs; (ii) perceptions of the positive and negative outcomes of AVs; and (iii) AV usage intentions. The classes were titled Non-adopters (29% of the sample), Ride-sharing (20%), AV ambivalent (19%), Likely adopters (17%), and First movers (14%). The results indicate the types of individuals who may be most likely to be early adopters and the implications for public policies designed to encourage socially optimal forms of adoption.